2020
DOI: 10.1111/ppc.12517
|View full text |Cite
|
Sign up to set email alerts
|

The relations of internet and smartphone addictions to depression, anxiety, stress, and suicidality among public university students in Klang Valley, Malaysia

Abstract: Purpose: This cross-sectional study examined the cyber-psychological correlates of depression, anxiety, stress, and suicidality among public university students in Klang Valley, Malaysia. Design and Methods: Participants were randomly selected using multi-stage sampling methods from three public universities in the study location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 41 publications
5
61
0
6
Order By: Relevance
“…38 In another study, it was reported that there was a positive and significant relationship between internet addiction and depression, anxiety, stress, and suicidal tendency. 6 As a result of this study, a relationship between internet addiction and suicidal ideation was found, and the result of the study, therefore, supports the general literature.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…38 In another study, it was reported that there was a positive and significant relationship between internet addiction and depression, anxiety, stress, and suicidal tendency. 6 As a result of this study, a relationship between internet addiction and suicidal ideation was found, and the result of the study, therefore, supports the general literature.…”
Section: Discussionsupporting
confidence: 85%
“…5 In a study conducted with university students in Malaysia, it was found that 9.6% of the students (n: 525) had a high degree of internet addiction. 6 Considering the studies conducted to analyze the relationship between university students and internet addiction in Turkey, in the study of Aslan and Yazıcı 7 (n: 910), it was found that the rate of internet addiction was 2% and that the rate of risky internet users was 20.9%. In the study of Karasu et al 8 (n: 473), it was stated that 29.4% of the students showed limited symptoms and that 5.7% were pathological internet users.…”
mentioning
confidence: 99%
“…Researchers have documented that stress is associated with MPA, and that MPA is associated with depression. For example, according to Wan et al, smartphone addictions are significantly positively associated with both depression and stress among Malaysian public university students (56). However, it is unclear if MPA mediates the relationship between PAS and depression.…”
Section: Mpamentioning
confidence: 99%
“…21 Mahasiswa atau individu yang sedang mengalami stres akan menggunakan internet, smartphone, dan bermain game online untuk mengurangi stres yang sedang dialami. 22 Namun, jika keadaan stres yang sedang dialami tidak ditangani dengan baik, akan menghabiskan lebih banyak waktu untuk menggunakan internet dan smartphone yang berakibat adiksi. 22 Adiksi internet dan smartphone dapat menyebabkan gangguan psikologis seperti depresi, kecemasan, stres, dan rasa ingin bunuh diri.…”
Section: Pendahuluanunclassified
“…22 Namun, jika keadaan stres yang sedang dialami tidak ditangani dengan baik, akan menghabiskan lebih banyak waktu untuk menggunakan internet dan smartphone yang berakibat adiksi. 22 Adiksi internet dan smartphone dapat menyebabkan gangguan psikologis seperti depresi, kecemasan, stres, dan rasa ingin bunuh diri. 22…”
Section: Pendahuluanunclassified